1996
DOI: 10.2134/jpa1996.0399
|View full text |Cite
|
Sign up to set email alerts
|

Weed Encroachment in Established Alfalfa as Affected by Cutting Frequency

Abstract: Crazing‐tolerant alfalfa (Medicago sativa L.) cultivars are more persistent than hay‐type cultivars under severe grazing pressure but the influence of defoliation on weed encroachment is not well defined. Our objective was to determine the effect of rest interval between cuttings on encroachment of large crabgrass [Digitaria sanguinatis (L.) Scop.1 or common bermudagrass [Cynodon dactylon (L.) Pers.] into a grazing‐tolerant alfalfa cultivar. We used small‐plot field experiments with four replications of ‘Alfag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
3
11
2
Order By: Relevance
“…These data are similar to those reported by Kust and Smith (1961), who found that harvesting alfalfa four times per year in Wisconsin led to lower yields than when harvested three times. Hoveland et al (1996) in Georgia and Sheaffer et al (2000) in Minnesota showed that the optimum harvest interval for alfalfa is about 35 d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are similar to those reported by Kust and Smith (1961), who found that harvesting alfalfa four times per year in Wisconsin led to lower yields than when harvested three times. Hoveland et al (1996) in Georgia and Sheaffer et al (2000) in Minnesota showed that the optimum harvest interval for alfalfa is about 35 d.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent research with Alfagraze showed that it tolerated weekly harvests in the greenhouse better than ‘Florida 77’ (Brummer and Bouton, 1992). An extension of this work in the field by Hoveland et al (1996) showed that Alfagraze had equal yields when harvested every 4 wk vs. every 6 wk during the growing season. Based in part on the research of Hoveland et al (1996), farmers in the lower Midwest often plant Alfagraze and other grazing‐type alfalfas, expecting that more frequent harvests (and in turn better quality forage) are possible with these cultivars without decreasing yields or stand persistence.…”
mentioning
confidence: 85%
“…Weeds compete with alfalfa for light, water, and nutrients [4] [5] and consequently reduce yield and forage quality [6]. Newly established stands are especially more vulnerable [7], but older stands [8] and frequently cut stands [9] [10] are also affected. Therefore, the first year of planting is very crucial in terms of crop establishment, biomass yield, and stand persistence of alfalfa.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, alfalfa survival was lower in treatments with a single yearly defoliation of alfalfa in Conservation Reserve Program than in treatments that had three to four cuttings per year (Sheaffer et al 1997). A lower frequency of defoliation in mixed alfalfa-grass stands improved yield (Bittman et al 1991;Hoveland et al 1996) and decreased grass encroachment (Comstock and Law 1948;Bates et al 1996;Hoveland et al 1996).…”
mentioning
confidence: 99%